Emergency Department Crowding: Factors Influencing Flow - Arkun, Alp (Department of Emergency Medicine, University of California, Irvine School of Medicine, 2010)
BACKGROUND: The objective of this study was to evaluate those factors, both intrinsic and extrinsic to the emergency department (ED) that influence two specific components of throughput: “door-to-doctor” time and dwell time. METHODS: We used a prospective observational study design to determine the variables that played a significant role in determining ED flow. All adult patients seen or waiting to be seen in the ED were observed at 8pm (Monday-Friday) during a three-month period. Variables measured included daily ED volume, patient acuity, staffing, ED occupancy, daily admissions, ED boarder volume, hospital volume, and intensive care unit volume. Both log-rank tests and time-to-wait (survival) proportional-hazard regression models were fitted to determine which variables were most significant in predicting “door-to-doctor” and dwell times, with full account of the censoring for some patients. RESULTS: We captured 1,543 patients during our study period, representing 27% of total daily volume. The ED operated at an average of 85% capacity (61–102%) with an average of 27% boarding. Median “door-to-doctor” time was 1.8 hours, with the biggest influence being triage category, day of the week, and ED occupancy. Median dwell time was 5.5 hours with similar variable influences. CONCLUSION: The largest contributors to decreased patient flow through the ED at our institution were triage category, ED occupancy, and day of the week. Although the statistically significant factors influencing patient throughput at our institution involve problems with inflow, an increase in ED occupancy could be due to substantial outflow obstruction and may indicate the necessity for increased capacity both within the ED and hospital.